2008
DOI: 10.1111/j.1440-1673.2007.01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastomas – Primitive neuroectodermal tumours in the adult population

Abstract: SUMMARYMedulloblastomas -primitive neuroectodermal tumours are rare in adults. This review will evaluate a single centre's experience with this malignancy. The medulloblastoma -primitive neuroectodermal tumour database was evaluated for all patients aged more than 18 years who were referred for management. Relevant information from the database was abstracted to provide a descriptive record of this malignancy. Between 1977-2004 there were 11 patients referred, 1 with persistent disease and 10 were eligible, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
4
6
0
2
Order By: Relevance
“…25 This study extends that data by including a larger and more contemporary patient cohort from two specialist neurooncology institutions treated with platinum-based chemotherapy. To the best of our knowledge, there is only one Australian contemporary study of adult medulloblastoma where combined modality treatment was based on non-platinum chemotherapy.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…25 This study extends that data by including a larger and more contemporary patient cohort from two specialist neurooncology institutions treated with platinum-based chemotherapy. To the best of our knowledge, there is only one Australian contemporary study of adult medulloblastoma where combined modality treatment was based on non-platinum chemotherapy.…”
Section: Discussionsupporting
confidence: 55%
“…To the best of our knowledge, there is only one Australian contemporary study of adult medulloblastoma where combined modality treatment was based on non-platinum chemotherapy. 25 This study extends that data by including a larger and more contemporary patient cohort from two specialist neurooncology institutions treated with platinum-based chemotherapy.…”
Section: Discussionsupporting
confidence: 55%
“…In adults, the effect of chemotherapy has not been reliably studied, thereby leading to the standard therapy being surgical resection and full-dose radiotherapy to the entire neuroaxis in PNET as there is typically a high penetrance of the CSF [6]. Several studies over the last few decades have shown a dose-dependent benefit of radiotherapy leading to long-term disease-free survival, with various studies using anywhere between 15- and 25-Gy dosages to higher dosages of 55 Gy [13, 14]. The patient in our case received two cycles of radiotherapy as described above, the doses of which certainly fall within these ranges.…”
Section: Discussionmentioning
confidence: 99%
“…La mayoría de los tumores se manifestaron como un síndrome de hipertensión intracraneal, similar a lo referido por otros autores y coincidiendo con la población pediátrica 5,13,43 . Entre otros hallazgos en acuerdo con la literatura se encuentran que más de la mitad de los pacientes tuvieron tumores localizados en uno de los hemisferios cerebelosos 3,4,9,11 , con una alta proporción de tumores con variedad histopatológica desmoplásica (figura 3) 8,11,23,33 .…”
Section: Discussionunclassified
“…La RT ha mejorado considerablemente el pronóstico de pacientes con meduloblastomas en los últimos 40 años, empleándose de manera estándar después de la cirugía, con disminución de su recidiva y aumento de la supervivencia tanto en niños como en adultos, utilizando actualmente sistemas de planificación del tratamiento conformado con el objetivo de respetar, en la manera de lo posible, el parénquima normal 5,41 . Motivado por la elevada tendencia de diseminación a través del LCR de estos tumores y de acuerdo a lo descrito por otros autores 11,23,31,43 , en nuestro centro se han aplicado protocolos con dosis de radiación al eje craneoespinal entre 30-36 Gy, y una sobreimpresión en fosa posterior entre 20-26 Gy; por lo tanto se administraron dosis totales a nivel de la fosa posterior entre 54-56 Gy, ya que se ha demostrado que dosis menores de radiación se relacionan con un peor pronóstico tanto en adultos 1,23,25 como en niños 48 . En niños con meduloblastoma la QT adyuvante ha demostrado con un nivel de evidencia grado 1 un aumento de la supervivencia cuando se administra en conjunto con la cirugía y la RT 46 .…”
Section: Discussionunclassified